Calcium-ion and calmodulin-dependent kappa-casein kinase in rat mammary acini. - Brooks, C L (1984)
A Ca2+- and calmodulin-dependent casein kinase specific for dephosphorylated bovine kappa-casein was identified in a microsomal fraction of mammary acini prepared from rats in late lactation. This phosphorylation has an absolute requirement for Mg2+ for either the basal or the Ca2+- and calmodulin-dependent activity. One-half of the maximal stimulation is achieved at a calmodulin concentration of 204nM in the presence of Ca2+. The Ca2+- and calmodulin-dependent kinase activity (but not the basal activity) is inhibited by trifluoperazine. The casein kinase is associated with a microsomal fraction enriched in markers for plasma membrane and Golgi (5'-nucleotidase and galactosyltransferase respectively). The activity of this casein kinase remains relatively constant throughout lactation, but declines dramatically in 24h when rats are removed from their pups. This activity may represent the physiological activity responsible in part or whole for kappa-casein phosphorylation occurring before micelle formation and milk secretion.